New insights into the feeding behaviour of the Japanese squid Todarodes pacificus paralarvae, and a combined analysis of metagenome and amino acid isotope ratios - Kohsuke Adachi; Yoshito Chikaraishi; Sinpei Nomura; Naoko Goto-Inoue; Nobuhiro Zaima; Yuki Kuriya; Michihiro Araki; Katsuji Morioka; Takashi Yanagimoto; Mitsuhiro Nakaya; Jun Yamamoto (PLoS ONE, 2026)
The Japanese flying squid Todarodes pacificus (Ommastrephidae) is a commercially and ecologically important species; however, there remains much room for investigation in its early life phase, especially its diet in wild environments. After excising the digestive gland (cecum sac) of wild paralarvae of T. pacificus using Laser Microdissection (LMD), the dietary species were estimated via metagenomic analysis. The 16S rRNA analysis predominantly detected Burkholderiales and Xanthomonadales , regardless of mantle length (ML) of T. pacificus and capture area. COI (Cytochrome c oxidase subunit I) analysis detected in various organisms including Discosea, Arthropoda, Nemertea, Porifera, golden algae, and fungi (Ascomycota and Basidiomycota), which were found irregularly. About half of the paralarval cecum sacs were found empty during the histological analysis. We also estimated the trophic position (TP) of wild paralarvae in the same sea region via stable isotope analysis of amino acids. The TP estimated was 3.0 for all larval groups regardless of ML, suggesting that the trophic tendency of paralarvae is carnivorous, likely feeding on herbivorous organisms. Taken together, our results suggest that the paralarvae feed mostly on various kinds of living herbivorous organisms and partly on detritus.